Analysis Of The Influence Of Digital Marketing On Increasing Msme In The Post-Pandemic Era: Study Literature Review - Tasya Ananda Setiawan; Siti Maymunah; Hasyim Muzadi; Abdi Azhari Hasibuan; Fiqran Al Mahri; Guntoro Guntoro (Sharing: Journal of Islamic Economics Management and Business, 2026)
This study aims to analyze the influence of digital marketing on the growth of MSMEs in the post-pandemic era. The method used is a literature review by examining various scientific journals, research articles, and relevant library sources. The data obtained were analyzed descriptively to identify the impact of digital marketing implementation on MSME development. The results of the study indicate that digital marketing has a positive impact on the growth of MSMEs, particularly in expanding market reach, increasing sales, strengthening customer relationships, and enhancing business competitiveness. Various studies reviewed also show that the use of social media, marketplaces, websites, and other digital platforms helps MSMEs conduct promotions more effectively and efficiently. Thus, digital marketing can be an effective strategy in supporting the growth and sustainability of MSMEs in the post-pandemic era and accelerating MSME adaptation to developments in the digital economy.